(untitled) (Economics and region, 2019)
The role of financial controlling as an integral part of the joint venture sustainable development management system is investigated in the article. The basic stages, concepts, functions, principles of formation and development of financial controlling are characterized. The necessity of organization is substantiated and the basic stages of introduction of financial control in management of development of joint venture are proposed.